Spatial implications of the organization of production in the automotive industry in Turkey - Aysenur Okten; B. Camlibel; Y. Evren; Betul Sengezer (European Regional Science Association (ERSA), 1998)
Since the 1980s, the restructuring tendencies of capital have been calling for the reorganization of production, reshaping of enterprises and reconsiderations of geographical space. Globalization and japanization emerged as the new concepts of the postfordist production era, the former implying the geographical enlargement of economic operations and markets while the latter representing a certain managerial model which has come to be considered a crucial element of the globalization process in the postfordist organization of production. Radical improvements in transportation and communication technologies resulted in the reduction of the associated costs which, in turn, made resources and markets all over the world accessible. However, this accessibility destroyed the oligopolistic advantages of business firms due to? their proximity to local markets (Thisse, 1994). Globalization forced them to seek for other types of competition whereby the survival of a firm depends on its performance in the diversity of its products, quality of goods and asociated services, its responsiveness to demand, ability to reduce lapse of time, and innovating capacity (Veltz, 1994). This new type of competitiveness requires intense interaction and cooperation inside firms, between various phases in the production cycle, between firms and their suppliers and clients, as well as between commodity markets and labour markets (Thisse, 1994). Thus, a new type of proximity becomes important for competitiveness. Territorial and local considerations are reinterpreted in reference to the global restructuring process of capital. Several questions are raised in this context: Will the big cities be increasingly interlinked in a global urban network? Will small towns which are not well linked to the network be facing increasing degeneration and poverty? What new links should be established between cities and their surrounding areas? (Derycke,1994). There are antithetic answers to those questions as far as urban hierarchy and local development is concerned. Some authors argue that the new form of competition would be to the detriment of traditional subcontracting networks based on proximity because of ?world sourcing?. Meanwhile, it would increase urban polarization because the new criteria of competitive survival and the need for flexibility against escalating uncertainty require location in large metropolises. On the other hand, other autors argue that ?global toyotaism, in comparison to global fordism, localizes more of the production process and therefore seems to be more conducive to local development in host nations? (Fujita&Hill, 1995). This paper attempts to analyse the spatial implications of the shift from fordist production to postfordist production, toyotaism in special, on the basis of data collected in the automotive industry in Turkey.
Keywords: 330